Multiple infusions of mesenchymal stromal cells induce sustained remission in children with steroid‐refractory, grade III–IV acute graft‐versus‐host disease. (31st August 2013) - Ball, Lynne M.; Bernardo, Maria E.; Roelofs, Helene; van Tol, Maarten J. D.; Contoli, Benedetta; Zwaginga, Jaap Jan; Avanzini, Maria Antonia; Conforti, Antonella; Bertaina, Alice; Giorgiani, Giovanna; Jol‐van der Zijde, Cornelia M.; Zecca, Marco; et al.
Summary: Mesenchymal stromal cell (MSC) infusions have been reported to be effective in patients with steroid‐refractory, acute graft‐versus‐host disease (aGvHD) but comprehensive data on paediatric patients are limited. We retrospectively analysed a cohort of 37 children (aged 3 months‐17 years) treated with MSCs for steroid‐refractory grade III–IV aGvHD. All patients but three received multiple MSC infusions. Complete response (CR) was observed in 24 children (65%), while 13 children had either partial ( n = 8) or no response ( n = 5). Cumulative incidence of transplantation‐related mortality (TRM) in patients who did or did not achieve CR was 17% and 69%, respectively ( P = 0·001). After a median follow‐up of 2·9 years, overall survival (OS) was 37%; it was 65% vs. 0% in patients who did or did not achieve CR, respectively ( P = 0·001). The median time from starting steroids for GvHD treatment to first MSC infusion was 13 d (range 5–85). Children treated between 5 and 12 d after steroid initiation showed a trend for better OS (56%) and lower TRM (17%) as compared with patients receiving MSCs 13–85 d after steroids (25% and 53%, respectively; P = 0·22 and 0·06, respectively). Multiple MSC infusions are safe and effective for children with steroid‐refractory aGvHD, especially when employed early in the disease course.